Making your mind molecules, motion, and memory - Eric R. Kandel, lecturer; Thomas M. Jessell, lecturer (Howard Hughes Medical Institute, 2009)
Eric R. Kandel and Thomas M. Jessell, two leading neuroscientists, discuss current understanding of memory and brain development.